Evaluation of Total Quality Management Opportunity Implementation and Its Effect on The School Administration Development A Field Study on Directors of The Secondary Stage Teaching in Lattakia - Tayoub, Mahmoud; Rahhal, Mario; Husien, Mahmoud Hasan (Latakia University Journal - Economic and Legal Sciences Series, 2019)
يهدف هذا البحث إلى التعرف على تقويم فرص تطبيق إدارة الجودة الشاملة وتأثيرها على تطوير الإدارة المدرسية من خلال عدة محاور: المناخ التنظيمي والإداري في المدرسة, العلاقة بين إدارة المدرسة والمعلمين, العلاقة بين إدارة المدرسة والطلاب, العلاقة بين إدارة المدرسة والمجتمع المحلي. وانتهى البحث إلى النتائج التالية: 1- وجود درجة عالية من الوعي لدى مديري مدارس التعليم الثانوي حول إمكانية تطبيق إدارة الجودة الشاملة ومبادئها في تطوير عمل الإدارة المدرسية. 2- عدم وجود فروق ذات دلالة إحصائية عند مستوى دلالة (0.05) بين متوسطات إجابات المديرين حول فرص تقويم تطبيق إدارة الجودة الشاملة تعزى لمتغيري الخبرة والمؤهل العلمي. This research aims to give an idea about opportunities of the evaluation of total quality management implementation and their effect on the development school administration from many points of view: the administrative and systemic order in the school, the relation between the school administration and the teachers, the relation between the school administration and the students and the relation between the school administration and the local society. The study concluded the following results: 1- The directors of Secondary Education Schools have a high degree of awareness of the effects of implementing the total quality management and its principles in developing the activity of school administration. 2- There are no significant statistical differences on the level (0.05) between the averages of the directors' answers about the opportunities of implementation of total quality management, which is related to the variables of experience and the scientific degree.